A developmental toxicity study of 3S, 3′S-Astaxanthin in New Zealand white rabbits. (April 2016) - Schneider, Steffen; Mellert, Werner; Schulte, Stefan; van Ravenzwaay, Bennard
Abstract: Astaxanthin, a naturally occurring pigment used to give the characteristic orange-pink colour to salmonid fish reared in aquaculture, is also marketed as a dietary supplement. Synthetic 3S, 3′S-Astaxanthin was tested for potential harmful effects on the in utero development of New Zealand white rabbits in a study according to international regulatory guidelines. There were two control groups, one being a placebo administration and three dose levels corresponding to 100, 200, and 400 mg of 3S, 3′S-Astaxanthin per kg body weight/day. The group sizes varied from 23 to 27 litters, providing approximately 200 fetuses per group for evaluation of developmental toxicity. There were no significant effects on the health of the does, nor on the size and viability of the litters. Malformations, both external and internal, were rare and occurred in all groups, including controls with no indication of a treatment relationship. Variations were much more common, being found in all litters. However, when examined by type and frequency, no pattern emerged indicating a relationship to administration of the test substance. It is concluded that administration of 3S, 3′S-Astaxanthin in a gelatin/carbohydrate powder formulation throughout pregnancy up to 400 mg/kg body weight/day is without harmful effects on reproduction or fetal development. Highlights: Synthetic Astaxanthin was investigated in a regulatory compliant developmental toxicity study in New Zealand White rabbits. Animals were treated from gestational days 6–28 by gavage with an Astaxanthin powder formulation or a blank formulation. Doses up to 400 mg/kg body weight throughout pregnancy did not indicate any potential risk of developmental toxicity.